Case Report: Coexistence of generalized arterial calcification of infancy (GACI) and maternal infections with cytomegalovirus and Toxoplasma gondii-unexpected fatal complication in a newborn - Gurzu, Simona; Burlacu, Diana; Sánta, Réka; Jung, Ioan; Slevin, Mark; Fulop, Emöke (Frontiers in Pediatrics, 2022)
Generalized arterial calcification of infancy (GACI) is an extremely rare autosomal recessive condition characterized by the storage of calcium at the level of internal elastic membrane of arteries. The main consequences are intimal fibrous thickening and arterial occlusion. We present the case of a preterm male infant, born from an improperly dispensed pregnancy. At birth, the newborn presented generalized edema and hypotonia, abolished heart sounds, without response to stimulation. Despite the mechanical ventilation, the infant died two hours after birth. The death was clinically presumed to be related to the maternal infection with cytomegalovirus (CMV) and Toxoplasma gondii. The infant’s mother affirmed the history of 6 previous miscarriages and the non-consanguineous marriage. At autopsy, microscopic examination showed generalized vasculitis secondary to myointimal calcification of the large and medium-sized vessels of the lungs, liver and tongue. These findings supported the diagnosis of GACI. Hydrothorax, non-infective ascites and necrosis of the brain parenchyma were also associated. The premature infant died due to tonsillar herniation associated with decreased vessel compliance and refractory pulmonary hypertension thus leading to congestive cardiac failure. CMV was not detected on histopathological assessment nor were signs of any other infections. To the best of our knowledge, this is the first case of GACI occurring in a baby from a mother co-infected with CMV and T. gondii.